A survey across four European countries to determine rheumatology health professionals' awareness of physical activity measures in people with inflammatory joint diseases. Issue 5 (31st May 2018) - Kennedy, Norelee M; McKenna, Sean G; O'Neill, Aoife; Appel Esbensen, Bente; Swinnen, Thijs Willem; Nordgren, Birgitta; Willemijns, Sara; Hammer, Nanna Maria; Brodin, Nina
Abstract : Objectives: The objectives of this study were to determine rheumatology health professionals' (HPs)' awareness of and confidence in using physical activity (PA) measures in people with inflammatory joint diseases (IJDs), their own self-reported PA levels and to identify HP-related educational needs. Methods: Rheumatology HPs in Denmark, Sweden, Ireland and Belgium participated in an on-line survey. Descriptive statistics and latent class analysis (LCA) were undertaken SPSS (v21and SASv9.4) to describe data aggregates and range and to identify subclasses of groups with respect to use of PA measures. Results: 322 (n=322, 75.5% women) HPs responded from Denmark (n=50, 15.5%), Sweden (n=66, 20.5%), Ireland (n=28, 8.7%) and Belgium (n=178, 55.3%) and the majority of respondents (n=286, 91.7%) reported it was important to measure PA in people with IJDs. Only 28.2% of HPs used simple body worn sensors to measure PA levels in their patients. The majority were interested in on-line education on measuring PA (82.9%). LCA, used to generate classes of PA measures employed by HPs, revealed three distinct classes reflecting differences in self-reported PA levels, awareness of PA measures, further education requirements and professional background. Conclusions: The majority of respondents reported that they considered measuring PA as important in people with IJDs; however, the majority lacked confidence in how to measure it. There was strong interest in further education around measuring PA. Three distinct respondent classes were identified to inform targeted education on how to measure PA.